2022
DOI: 10.21037/gs-21-708
|View full text |Cite
|
Sign up to set email alerts
|

A narrative review of current therapies in unilateral recurrent laryngeal nerve injury caused by thyroid surgery

Abstract: Objective: To summarize and compare current common treatments in recurrent laryngeal nerve injury (RLNI). In addition, we introduced nerve tissue engineering technology in RLNI animal models. This review is a comprehensive summary of current therapies for unilateral RLNI.Background: RLNI is a common complication in thyroid surgery. Although preoperative imaging and intraoperative nerve monitoring are widely applied, some damage to nerves is still inevitable. Currently, advances in nerve repair and regeneration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Recurrent laryngeal nerve (RLN) injury impairs vocal cord mobility, resulting in incomplete glottic closure, potentially causing hoarseness, dysphagia, and sometimes aspiration pneumonia, decreasing the patient's quality of life. RLN injury has several causes, including thyroid cancer surgery 1–4 . If thyroid cancer or metastatic lymph nodes directly invade the RLN, it may be resected for curative oncological purposes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recurrent laryngeal nerve (RLN) injury impairs vocal cord mobility, resulting in incomplete glottic closure, potentially causing hoarseness, dysphagia, and sometimes aspiration pneumonia, decreasing the patient's quality of life. RLN injury has several causes, including thyroid cancer surgery 1–4 . If thyroid cancer or metastatic lymph nodes directly invade the RLN, it may be resected for curative oncological purposes.…”
Section: Introductionmentioning
confidence: 99%
“…In such cases, immediate intraoperative reconstructive procedures such as direct anastomosis (DA) and ansa cervicalis to RLN anastomosis (ARA) may improve speech function and prevent aspiration compared to delayed repair procedures such as injection laryngoplasty and medialization thyroplasty. From this perspective, immediate intraoperative repair of RLN has more advantages than disadvantages and 5,6 should be performed whenever possible 1,2,7,8 …”
Section: Introductionmentioning
confidence: 99%
“…Tissue engineering has been researched extensively in several regenerative techniques, including cartilage, neuron, cardiac, and bone regeneration [ 7 , 8 , 9 , 10 ]. Nonetheless, previous studies [ 11 , 12 , 13 , 14 ] have identified vocal fold fibroblasts, muscle progenitor cells, embryonic stem cells (ESCs), bone marrow mesenchymal stem cells (BMMSCs), and adipose stem cells (ASCs) with or without the use of a scaffold as a delivery vehicle for vocal fold regeneration. This study seeks to outline the most recent advancements in injectable biomaterials that transport biomolecules and cells for regeneration purposes and to identify future directions for tissue engineering–based treatment of glottic insufficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Given the morbidity that RLN injury carries for patients, there exists a number of conservative and surgical therapies for RLN healing (7), as well as a growing interest in innovative therapies involving electrical stimulation and tissue engineering (8,9). However, these therapies are limited physiologically, as axonal regeneration is generally limited and slow (10).…”
Section: Introductionmentioning
confidence: 99%
“…3,4 The introduction of intraoperative nerve monitoring aimed at RLN preservation has been largely equivocal based on recent meta-analyses, and the incidence of RLN injury during thyroid surgery has remained relatively stable. 5,6 Given the morbidity that RLN injury carries for patients, there exists a number of conservative and surgical therapies for RLN healing, 7 as well as a growing interest in innovative therapies involving electrical stimulation and tissue engineering. 8,9 However, these therapies are limited physiologically, as axonal regeneration is generally limited and slow.…”
mentioning
confidence: 99%